Estudio técnico para mejorar los métodos de trabajo en el proceso de fabricación de pallets de la Empresa Kilumba S.A del cantón Quevedo provincia de Los Ríos, año 2014 - López Triana, Gonzalo Omar (2015)
The present research had as main aim to establish a technical study to improve the working methods in the manufacturing process of pallets Company SA Quevedo canton Kilumba year 2014.Tuvo objectives an analysis of the current status of methods of work being done on the ground, in order to determine the capacity of the machines, processes each establishment of pieces of each area by determining the level of productivity, in order to improve the process and profitability in manufacturing pallets. The result of the survey reached to determine, in the machinery is not performed since the preventive keeping these tiny suffer damage, so causing the process stops also not trained operators, which generate little knowledge processing parts. Furthermore, it was evident that in each machining area there are several engines that are misplaced in position on each pallets process; not all of them need a higher capacity engine for hard work, as in other areas are needed to take advantage of these engines for greater speed logs and improve production capacity. With regard to the process of pallets on the ground, it became clear that the travel time on production lines from delivery of raw materials to delivery of the finished product is content hundred and four minutes, which indicates the diagram current process, if the business would on their part to implement new working methods addressed the flowchart well get a favorable increase achieving greater productivity.